2005
DOI: 10.1002/jmv.20487
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of hepatitis E virus in Darfur, Sudan, and neighboring Chad

Abstract: The within-outbreak diversity of hepatitis E virus (HEV) was studied during the outbreak of hepatitis E that occurred in Sudan in 2004. Specimens were collected from internally displaced persons living in a Sudanese refugee camp and two camps implanted in Chad. A comparison of the sequences in the ORF2 region of 23 Sudanese isolates and five HEV samples from the two Chadian camps displayed a high similarity (>99.7%) to strains belonging to Genotype 1. But four isolates collected in one of the Chadian camps wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 7 publications
1
53
0
1
Order By: Relevance
“…Other HEV-2 strains have appeared in Africa, where they have also been implicated in outbreaks (57,58).…”
Section: Epidemiologic Patterns Of Hepatitis E Virus Infectionmentioning
confidence: 99%
“…Other HEV-2 strains have appeared in Africa, where they have also been implicated in outbreaks (57,58).…”
Section: Epidemiologic Patterns Of Hepatitis E Virus Infectionmentioning
confidence: 99%
“…Genotype 2 sequences were first reported from an epidemic in Mexico (Huang et al 1992) and subsequently identified from endemic cases in several African countries (Buisson et al 2000;Maila et al 2004;Nicand et al 2005). Genotype 3 is widely distributed and has been isolated from sporadic cases of acute human HEV infection and /or domestic pigs in several countries throughout the world (Okamoto, 2007).…”
Section: Geographical Distributionmentioning
confidence: 99%
“…2 Epidemics of HEV have been reported in African countries, including Sudan, Ethiopia, Somalia, Chad, the Democratic Republic of the Congo, and Uganda. [3][4][5][6] HEV infection in pregnancy can progress to fulminant hepatitis with a high mortality rate among pregnant women. [7][8][9] A recent study showed that pregnant Indian women with acute hepatitis E virus infection had a three times higher relative risk for fulminant hepatic failure and a six times higher risk for mortality.…”
Section: Introductionmentioning
confidence: 99%